Study on Automatic Platform Gate (APG) Door Rubber Alternative Design of MRT SSP Line Project - Hamka, Muhammad Auris; Hasnan, Khalid (Progress in Engineering Application and Technology, 2022)
As APG being tested its functionality of the systems, the cyclic test being held for about 1000 times in System Acceptance Test (SAT). When running the cyclic test for a long time, the rubber door or door rubber strip, which installed as an anti-collision rubber, can slide down and touch the insulation mat of threshold. Therefore, the structure of the Automatic Sliding Gate (ASG) needs to re-designed in this project. The purpose of this work is to propose the new design of ASG structure that can hold the door rubber from sliding down. The new design of ASG will have three vertical-square holes that provide alternative solution to eliminate the slot frame, which function to hold the rubber door on the ASG frame. The best design will be chosen based on its performance from gravitational simulation test, either the current or new design of rubber door. The objective of this project is being achieved as discussed in this project. The new design of door rubber gives better comparison than the current door rubber design on the gravitational simulation test.